Implementation of the Trade Facilitation Agreement in the Republic of Macedonia - Toshevska trpchevska, Katerina (Економски факултет, Универзитет „Св. Кирил и Методиј“, Скопје, 2017)
In this paper, we analyze the effects of the implementation of certain trade facilitation measures in the Republic of Macedonia. According to its commitments to abide by the recommendations of the World Customs Organization and the World Trade Organization, the Republic of Macedonia has implemented most of the trade facilitation measures mentioned in the provisions of the WTO Trade Facilitation Agreement. As of February 2017, the Trade Facilitation Agreement came into force after two-thirds of the WTO Member Countries have ratified it. This is why we think it is important to make an analysis and revision of the already implemented measures and provide some insight on their influence over foreign trade operations in Macedonia. Measures that we plan to elaborate in the paper refer to the single-window system, simplified customs procedures, risk management practices, and application of the EU’s New Computerized Transit System. The goal of this paper is to point out to the inefficiencies and possible future improvements of the related measures, by providing insight of their functioning.
Keywords: Trade Facilitation Agreement, Republic of Macedonia, EXIM, simplified customs procedures, risk management techniques